IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR PAB 19 BANDAR KHALIFAH - Mitha Shaskila Sinaga (Kuttab : Jurnal Ilmu Pendidikan Islam, 2023)
Abstract:Implementation of the 2013 Curriculum in Islamic Religious Education Subjects. This study used a descriptive method with a qualitative approach which was carried out at SD PAB 19 Bandar Khalifah. Through this research analysis it is hoped that it can be used as reference material regarding the implementation of the 2013 curriculum, especially in Islamic Religious Education lessons. From the analysis of this research that has been done, it can be concluded that the implementation of the 2013 curriculum is relevant to Islamic religious education lessons in elementary school education units because it trains or develops students' abilities to be more active.Â